2022
DOI: 10.1002/cmdc.202100679
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the IspD Enzyme in the MEP Pathway: Identification of a Novel Fragment Class

Abstract: The enzymes of the 2‐C‐methylerythritol‐d‐erythritol 4‐phosphate (MEP) pathway (MEP pathway or non‐mevalonate pathway) are responsible for the synthesis of universal precursors of the large and structurally diverse family of isoprenoids. This pathway is absent in humans, but present in many pathogenic organisms and plants, making it an attractive source of drug targets. Here, we present a high‐throughput screening approach that led to the discovery of a novel fragment hit active against the third enzyme of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It has been suggested that high levels of transporters are involved in cell detoxification, nutrient recycling, and antibiotics and drug efflux, significantly affecting the survival and development of multiple drug-resistant strains in Mtb [58,59,62,63]. It should be noted that the unique genes identified 2-C-methyl-D-erythritol 4-phosphate cytidylyltransferase and Arylamine N-acetyltransferase were previously characterized as high-confidence drug targets [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that high levels of transporters are involved in cell detoxification, nutrient recycling, and antibiotics and drug efflux, significantly affecting the survival and development of multiple drug-resistant strains in Mtb [58,59,62,63]. It should be noted that the unique genes identified 2-C-methyl-D-erythritol 4-phosphate cytidylyltransferase and Arylamine N-acetyltransferase were previously characterized as high-confidence drug targets [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that more electronwithdrawing substituents, such as a nitro (8) or nitrile group (10), had a pronounced effect on the potency, resulting in a factor 400 increase (e.g., 8, PfIspD IC50 = 41 ± 7 nM). While substituents with a less distinct electronwithdrawing effect, such as the trifluoromethyl (11) and the chloride (5), had a smaller effect on the potency (e.g, 11, PfIspD IC50 = 91 ± 19 nM). Lastly, weak donating groups, such as the methyl (6), had an even smaller increase in potency (e.g, 6, PfIspD IC50 = 370 ± 80 nM), but were still significantly better than the initial hit compound 4.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the MEP pathway is absent in human cells, mitigating the risk of off-target side effects, hence making it a source of promising drug targets. 4,5 Validation of the MEP pathway enzymes as drug target is based on fosmidomycin, an inhibitor of the second protein, IspC or DXR, of the MEP pathway. Currently in second-phase clinical trials as a combination treatment for malaria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For most bacteria and Apicomplexa parasites, the MEP pathway is the only route for the biosynthesis of IPP and DMAPP and has therefore been identified as an interesting target for the development of new antibiotics and antiparasitic drugs [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The MEP pathway in Plasmodium starts with the condensation of pyruvate and glyceraldehyde 3-phosphate (G3P), which yields DXP as a key metabolite.…”
Section: Introductionmentioning
confidence: 99%